The relationship between parental emotional abuse and interpersonal competence and digital game addiction: A path analysis - İbrahim Taş (Indian Journal of Psychiatry)
Background: Digital game addiction is a negative effect of the technological developments that have taken place and has been reported in literature as a serious mental health problem for children and adolescents in the developmental period. Aim: This study investigates the relationship between perceived emotional abuse from parents and interpersonal competence and game addiction by using a model. Methods and Material: The study group comprised 360 adolescents, with 197 (54.7%) being female and 163 (45.8%) male. The adolescents’ ages varied between 13 and 18 and their average age was 15.55. The data were collected using Psychological Maltreatment Questionnaire, Interpersonal Competence Scale, and Game Addiction Scale. The relationship between variables was tested using structural equation modeling. Results: The emotional abuse perceived from the mother significantly influences interpersonal competence and game addiction. Emotional abuse perceived from the father significantly influences game addiction. Interpersonal competence negatively influences game addiction at a significant level. Interpersonal competence mediates the relationship between maternal emotional abuse and digital game addiction. Conclusions: Maternal emotional abuse has been effective in decreasing interpersonal competence levels in adolescents. Parental emotional abuse is effective in game addiction in adolescents. Low level of interpersonal competence among adolescents affects game addiction. Emotional abuse perceived from the mother affects digital game addiction through interpersonal competence. Accordingly, educators, researchers, and clinicians dealing with digital game addiction in adolescents should consider the effect of perceived parental emotional abuse and interpersonal competence.